Дослідження геоелектричними методами інженерно-геологічного стану південно-західного Кривбасу. Частина 1. Фізико-геологічні передумови досліджень - Пігулевський, П.Г.; Свистун, В.К.; Кирилюк, О.С. (Геоінформатика, 2016)
Проаналізовано можливості ефективного використання геоелектричних методів для комплексного вивчення впливу техносфери на геологічне середовище Кривбасу з метою вирішення завдань екологічної безпеки. Як приклад розглянуто результати виконання робіт геоелектричними методами Дніпропетровською геофізичною експедицією “Дніпрогеофізика” під час вивчення інженерно-геологічних умов південно-західної частини Кривбасу, і передусім гідрогеологічних. Аналіз наявної петрофізичної та інженерно-гідрогеологічної інформації дав змогу вибрати оптимальні електророзвідувальні параметри установки вертикального електричного зондування (ВЕЗ) та природного поля (ПП). Досліджувана територія зазнає великого техногенного навантаження, а також впливу природних геологічних процесів (карстоутворення, неотектонічна активність), які контролюють поверхневий та підземний розподіл води. Викладено петрофізичні та інженерно-гідрогеологічні дані щодо території південно-західної частини Кривбасу і можливості геоелектричних методів для визначення рівня стояння підземних вод: методика виконання польових робіт, результати обробки та інтерпретації даних цих методів. Анализируются возможности эффективного использования геоэлектрических методов с целью комплексного изучения влияния техносферы на геологическую среду Криворожского железорудного бассейна (Кривбасса) и решения задач экологической безопасности.В качестве примера рассмотрены результаты исследований геоэлектрическими методами, проведенных Днепропетровской геофизической экспедицией “Днепрогеофизика” при изучении инженерно-геологических условий юго-западной части Кривбасса, и прежде всего гидрогеологических.Изучены и систематизированы сведения по дифференциации геоэлектрических характеристик осадочных и кристаллических пород. Анализ имеющейся петрофизической и инженерно-гидрогеологической информации позволил выбрать оптимальные электроразведочные параметры установки вертикального электрического зондирования (ВЭЗ) и естественного поля (ЕП), что дало возможность решить поставленные задачи для территории, которая характеризуется большой техногенной нагрузкой. Последняя оказывает влияние и на протекание современных геологических процессов (карстообразование, неотектоническая активность), контролирующих поверхностное и подземное водное распределение. В первой части статьи изложены петрофизические и инженерно-гидрогеологические сведения юго-западной части Кривбасса и возможности геоэлектрических методов при изучении уровня стояния подземных вод: методика выполнения полевых работ, результаты обработки и интерпретации исследований указанными методами. The purpose of the investigation is to analyze and generalize physical properties of rocks, geological and geophysical data. We based the study on the results obtained in the previous years. Data systematization permitted toselect geophysical methods for studying the geological conditions of the Kryvbas south-western part.
Method. The petrophysical, engineering and hydrogeological data analysis of the sedimentary rocks allowed to choose optimal geoelectric parameters for the vertical electrical sounding (VES) instrument. Calculations showed the optimal instrument, which is symmetrical installation AMNB with equipment ANC-3 with spacing AB length of 300 m long. The observation step is 200 m. We performed 33 crusades VES in the points near the previously drilled wells. This stage of the research was performed to compare electrical and geological parameters (geological strata boundaries and their bulk) under the qualitative and quantitative interpretation of VES and to study rocks anisotropy. Four years later the repeated linear VES were carried out on the main profiles. This study was conducted to determine the geoelectric rock parameters changes associated with the spatial-temporal changes in hydrogeological conditions of geological environment.
Results. The geological and geophysical sections of the first stage of our research were constructed as a result of VES electrical qualitative and quantitative interpretation. This data gave us information about the aquifer system structure and Neogene-Quaternary parameters of the sediments. In the second stage we used these sections as a basis of complex geophysical interpretation. The obtained results will be discussed in the second part of the paper.
The practical significance and conclusions. The proposed technology can rapidly detect and map the flooding zones by the geoelectric methods. The complex study is important in investigating the technosphere impact on the Kryvbas geological environment and in making environmental safety decisions.